10.21474/IJAR01/20053 - C.K Kouakou; T.E Manle; BTA Zaouli; L. Fondio (International Journal of Advanced Research, 2024)
In Cote dIvoire, mango is the 2nd most fruit export after bananas, with national exports estimated at 32,811 tonnes. Ivorian exports of mango mainly concerns three varieties: Kent, Keitt and Amelie. However, other untapped varieties could offer more interesting than those mentioned above. The aim of the present study is tto contribute to the selection of early varieties with characteristics attractive to the European market. The work was carried out over two consecutive years from the 128-variety mango collection of the Centre National de Recherche Agronomique (CNRA) in Lataha. For each variety, the parameters measured concerned fruit evaluation criteria. Statistical analysis was carried out to describe the agro-morphological variability of the varieties. The variances observed between mango trees were significantly explained by fruit mass, width and circumference, Â°Brix and fruit dry matter. The results identified 24 early varieties. Agro-morphological characterization showed that these varieties have a mass (MaFr) ranging from 60.8g to 637.007g. The hierarchical classification resulted in 3 groups: Group III comprises off-caliber varieties (200g) and A-caliber varieties (200 to 350g), Group II comprises B-caliber varieties (351 to 550g) and Group I compares C-caliber varieties (551 to 800g). Their sugar content (BrixFr) varies from 16.05% to 26.08% depending on the variety, offering a wide range of tastes. These results indicate the high potential of these varieties in the selection of new varieties.